Mechanisation and productivity in the linen industry - Larmor, Graham (Statistical and Social Inquiry Society of Ireland, 1955)
In considering what I have to say to-night, I would like it to be clearly appreciated from the outset that the business of growing and processing flax?its conversion into yarns?their later weaving into linen fabrics?and the final cloth-bleaching, dyeing, and finishing processes constitutes a craft trade of a very high order. It is essential to keep this fact prominently in mind, for it severely limits the extent to which productivity in the industry can be increased by a process of mechanisation similar to that which has taken place in the manufacture of rayon or cotton. For this reason the manufacture of linen, particularly in the fine end of the trade associated with Northern Ireland, involves a much higher proportion of operatives to machinery than rules in the cotton trade of Lancashire, or in the rayon industry.
Read before the Society in Belfast on 12th November 1954
Keywords: Linen industry, Northern Ireland; Mechanisation; Productivity; 314.15